Security of cloud computing: belongings for the generations - Jabbar, Jahangir; Mehmood, Hussain; Malik, Hassaan (International Journal of Engineering and Technology, 2020)
Cloud computing plays an important role in Information Technology (IT) management. Consequently, various cloud computing developers and users experience different benefits and similarly challenges to its use and potential opportunities in driving the Fourth Industrial Revolution. Despite the increasing benefits of cloud computing, including increased speed of data processing and reduced costs compared to traditional computing, issues of security and privacy risk remain one of the greatest concerns in cloud computing. Through a systematic literature review, the evolution and developments in technology and issues of security and privacy from many years are examined to establish the trends in the threats; and thereby, provides a projection on the future of security of cloud computing. This paper presents the cloud computing aspects (types/aspects, and categories such as Infrastructure as a Service (IaaS), Platform as a Service (PaaS) and Software as a Service (SaaS). The paper dwells on the challenges of cloud computing going into the future with some solutions that have potential to work.Â Â Â